“Muda dan Merakyat”: Political Campaign Posters Affecting The Indonesian General Election - Utomo, Aries (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Poster is the most media used during political campaigns to introduce legislative and executive candidates in public space. This study aims (1) to portray political campaign posters affects to attract voters living in villages or remote areas during 2024 Indonesian general election, and (2) to describe those posters that are situated in public spaces. Belimau street located in the Northern of Samarinda city, East Kalimantan Province, Indonesia was involved as the research object. Affective regime and linguistic landscape approach were utilized to conduct this study. Photography and walking were utilized to collect poster data alongside the street, then analyzed linguistically and non-linguistically by using Miles and Huberman model (i.e., displaying, reducing, and conclusion). Based on the findings, it can be identified that (1) there -are four kinds of affects dominantly identified, i.e., Young and Popular, Sustainability, Local Identity, and Change and Restoration, and (2) most political campaign posters are situated in strategic areas (e.g., main street or commercial site) with attractive design and language choice. This media is believed to be an effective way to attract voters living in villages or remote areas that are not interested in social media (e.g., Facebook, Instagram, or X).